CONNECTING WITH A HUMAN TOUCH - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, June 2017 - Some 40 Universiti Sains Malaysia (USM) Graduate School of Business (GSB) Master of Business Administration (MBA) students and academic staff participated in the Community Outreach Programme at the Cerebral Palsy (Spastic) Children’s Association of Penang last month.